Building Rural Household Resilience Due to Environmental Changes in the Hadejia-Nguru Wetlands, Northeastern Nigeria - Galtima, M.; Tafida, A.A. (Journal of Management and Development Studies, 2016)
Environmental changes in the Hadejia-Nguru wetlands have grossly affected the functionality of the ecosystem with multiplier effects on livelihoods of more than 1.5 million people. The most critical change occurred through the invasion of the water bodies by Typha grass, which has hampered the predominant activities, fishing and farming, thereby subjecting the people into abject poverty conditions. This has attracted the attention of Nigerian Government, International Development Agencies and Non-Government Organizations in designing and implementing several intervention measures. In many communities, the failure of the interventions in up-lifting the quality of life has been attributed to the wetlands resource utilization strategies prescribed. This study uses the concept of sustainable livelihood framework by focusing on the occurrence of Typha grass (external vulnerability factor), capital assets and policy/institutional structures to construct alternative livelihood strategy model in order to develop household resilience against environmental changes. Data for the study was obtained from household surveys in fifteen communities of the wetlands region and analyzed using descriptive statistics, multiple regression and Foster Greer Thorbeke models. The results indicate that a combination of five capital assets: physical (power, road and markets); human (experience, skills and schooling), social (cooperative, remittance and linkages), natural (land, forest and fisheries); and financial (savings, disposables, credit) resources serve as the optimum factors in yielding higher incomes and thus developing a resilience against environmental vulnerability and poverty.